Fleet sizing in loading and hauling operations using systems simulation models - Lins de Noronha, Osmar (2018)
The present study addresses aspects that must be considered in the sizing of the equipment for material loading and haulage (ore and waste) in an open-pit mine in the Central-West Region of Brazil. This is a complex process because a significant number of variables that limit the activities intrinsic to the loading and hauling operations are involved in the analysis. Such variables are: production rates per unit of time, physical-mechanical characteristics of the material, hauling distances, topography, access design, hauling routes, cycles, and fleet performance (truck, shovel). Additionally, there are other external variables that also condition a normal operation, such as rain, snow, fog and seismic movement. The purpose of this study is to size the fleet of the loading and hauling equipment that fulfills the processing plant requirements in an efficient manner.